Prevalence and Correlates of Bipolar Spectrum Disorder in the World Mental Health Survey Initiative - Merikangas, Kathleen R. (2011)
CONTEXT: There is limited information on the prevalence and correlates of bipolar spectrum disorder in international population-based studies using common methodology. OBJECTIVE: To describe the prevalence, impact, patterns of comorbidity, and patterns of service utilization for bipolar spectrum disorder in the WHO World Mental Health survey (WMH) initiative. DESIGN: Cross-sectional face-to-face household surveys PARTICIPANTS: 61,392 community adults in 11 countries in the Americas, Europe, and Asia MAIN OUTCOME MEASURE: DSM-IV disorders, severity, and treatment assessed with the World Mental Health version of the WHO Composite International Diagnostic Interview (WMH CIDI 3.0), a fully-structured lay-administered psychiatric diagnostic interview. RESULTS: The aggregate lifetime prevalence of BP-I disorder was 0.6%, BP-II was 0.4%, subthreshold BP was 1.4%, and Bipolar Spectrum (BPS) was 2.4%. Twelve-month prevalence of BP-I disorder was 0.4%, BP-II was 0.3%, subthreshold BP was 0.8%, and BPS was 1.5%. Severity of both manic and depressive symptoms, and suicidal behavior increased monotonically from subthreshold BP to BP-I. By contrast, role impairment was similar across bipolar subtypes. Symptom severity was greater for depressive than manic episodes, with approximately 75% of respondents with depression and 50% of respondents with mania reporting severe role impairment. Three-quarters of those with BPS met criteria for at least one other disorder, with anxiety disorders, particularly panic attacks, being the most common comorbid condition. Less than half of those with lifetime BPS received mental health treatment, particularly in low-income countries where only 25% reported contact with the mental health system. CONCLUSIONS: Despite cross-site variation in the prevalence rates of bipolar spectrum disorder, the severity, impact, and patterns of comorbidity were remarkably similar internationally. The uniform increases in clinical correlates, suicidal behavior and comorbidity across each diagnostic category provide evidence for the validity of the concept of a bipolar spectrum. BPS treatment needs are often unmet, particularly in low-income countries.